Application of high-quality nursing under the humanistic care nursing model in hospitalized elderly patients with chronic diseases (人文关怀护理模式下的优质护理在住院老年慢性病患者中的应用效果) - LI Yueru (李月茹); CAO Hongjing (曹红京); LI Ning (李宁); LI Jing (李静); PENG Kun (彭堃) (Association of Integrative Nursing, 2024)
Objective To investigate the effect of high-quality nursing services under the humanistic care nursing model for hospitalized elderly patients with chronic diseases. Methods Totally 70 elderly patients with chronic diseases admitted to the hospital from January 2022 to January 2023 were selected as the research objects. They were randomly divided into the study group and the control group, with 35 patients in each group. Patients in the control group received routing nursing interventions, and those in the study group were given high-quality nursing services under the humanistic care nursing model. The nursing quality evaluation criteria and self-made questionnaire were used to measure the quality of nursing service and patients' satisfaction. Results The score of nursing quality evaluation criteria in the study group was higher than that in the control group, with a significant difference(P<0. 01) . The overall satisfaction rate of the study group was higher than that of the control group (P＜0. 05). Conclusion Implementing the humanistic care nursing model is beneficial for improving the quality of nursing, increasing the patients' satisfaction with nursing services, and enhancing the nurse-patient relationship. (目的 探讨人文关怀护理模式下的优质护理服务在住院老年慢性病患者中的应用效果。方法 选取医院2022年1月-2023年1月收治的70例老年慢性病患者为研究对象, 随机分为研究组和对照组, 每组35例。对照组接受常规护理, 研究组在对照组的基础上实施人文关怀模式下的优质护理干预。采用优质护理质量评价标准评价服务质量, 调查患者对护理服务的满意度。结果 研究组护理质量评分高于对照组, 差异有统计学意义(P <0. 01)。研究组护理满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 实施人文关怀护理模式有利于提升护理质量, 提高老年慢性病患者对护理服务的满意度, 增进护患关系。)